A Reconfigurable Antenna-Based Solution for Stationary Device Authentication in Wireless Networks - Prathaban Mookiah; Kapil R. Dandekar (International Journal of Antennas and Propagation)
Applying channel information for user authentication is gaining attention in the area of wireless network security. Similarly, reconfigurable antennas capable of generating multiple decorrelated channel realizations have become increasingly popular in wireless systems. In this paper we propose and evaluate a channel-based authentication scheme that applies the capabilities of a pattern reconfigurable antenna for improved performance in user authentication. Field measurements of the channel frequency response employing such an antenna were performed to quantify the performance of the proposed scheme. Based on these measurements, we show the effect of correlation that exists between the different modes on the authentication performance. Furthermore, the performance gain that can be achieved by the scheme is studied as a function of the number of antenna modes. Offline mode analysis is performed to give a loose upper bound on performance while online mode analysis results are presented to quantify achievable authentication performance in realtime. A general guideline on how to choose the different elements of the decision metric in order to realize better performance for physical layer-based authentication schemes based on any diversity scheme is also developed.